THE CULTURAL AND IDEOLOGICAL PRECONDITIONS FOR ECONOMIC DEVELOPMENT: A COMPARATIVE STUDY OF THE JAPANESE AND THE SINHALESE BUDDHIST COMMUNITY OF SRI LANKA - Chandraprema, C.A.P.P (A thesis submitted for Faculty of Graduate Studies, 1999)
Japan is one of the success stories in Asia, being the first non-Western country to achieve the status of an economic superpower. Sri Lanka on the other hand, fell behind after independence. The reason for this decline was not the lack of 'objective' conditions for economic development but rather due to the absence of the subjective conditions. Max Weber always stressed the primacy of the subjective factor as against the objective factors in the process of economic development. The objective of this study would be to examine the cultural and ideological preparedness of the Sinhalese Buddhist majority community of Sri Lanka to embark on the path towards economic development within the universe of discourse opened up by Weber with his 'Protestant ethic' thesis. The following facts emerge.